Students™ Difficulties in Translating Idiomatic Expressions in English Narrative Text (TRANSFORM: Journal of English Language Teaching and Learning, 2024)
This study aimed at investigated the students' difficulties in translating idiomatic expressions in English narrative text and discovered its causes. The descriptive qualitative research design with research instruments in the form of questionnaires and interview guides was employed in this study. The source of data from this study was 33 students from the class XI IPA 1 of SMA Kartika I-2 Medan. This study found that the difficulties that arise when students translate narrative texts with idiom expressions in them are; (1) No equivalents in the TL for idiomatic expressions in the SL, (2) The context of idioms in SL and TL are different, (3) Idioms appear as its literal and idiomatic senses, and (4) The convention differences of using idioms in writing discourse. This difficulty was felt by 29 of the 33 students in the classroom. In addition, during the translation process, it was found that students can felt more than one form of difficulty when translating a narrative text. Then, this study also found that the most frequent reasons for this difficulty factor are students who do not understand what English idioms really are and also the difficulty of distinguishing English idioms from other sentences that are not idiomatic expressions.
Keywords: Idiomatic Expressions; Students’ Difficulties; Translation